2016
DOI: 10.1016/j.icheatmasstransfer.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A new model for density of nanofluids including nanolayer

Abstract: Nanofluids which are suspension of nanoparticles in conventional heat transfer fluids attracted researchers while they show higher thermal conductivity and specific heat capacity. The important parameters have influence on thermal-fluid properties of nanofluids include the volume fraction of the nanoparticles, temperature, density of fluid base and nanoparticles, nanoparticles size, nanolayer, thermal conductivity of base fluid and particles, and pH. Nanolayer which is an approved interfacial layer between par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…There are limited number of correlations available, for the effective density of nanofluid, that takes into account the particle size and shape, nanofluid temperature, added surfactant, and the nanolayer between the particles and the basefluid effect [213,214]. Hence more work is needed in this area to insure a much accurate prediction of the effective density at higher particles concentrations.…”
mentioning
confidence: 99%
“…There are limited number of correlations available, for the effective density of nanofluid, that takes into account the particle size and shape, nanofluid temperature, added surfactant, and the nanolayer between the particles and the basefluid effect [213,214]. Hence more work is needed in this area to insure a much accurate prediction of the effective density at higher particles concentrations.…”
mentioning
confidence: 99%
“…Density relates directly to the Nusselt number ( Nu ), Reynolds number ( Re ), pressure drop and friction factor of NF in CNT. Experimental measurements of the densities of NF and HNF have been carried out using different base fluids and NP or HNP at various temperatures and volume/mass concentrations or fractions [ 22 , 33 , 47 , 73 , 117 , 123 , 124 , 125 , 126 , 127 , 128 ]. The literature showed that the density of NF and HNF enhanced with the dispersion of NP or HNP in the different base fluids and detracted with a rise in temperature.…”
Section: Thermophysical Properties Of Nanofluids and Hybrid-nanoflmentioning
confidence: 99%
“…Therefore, updated mixture properties are required to be implemented. The mixture correlation is borrowed from the model developed by Sharifpur et al [49].…”
Section: Mixture Propertiesmentioning
confidence: 99%